Strategi Pemasaran Digital untuk Meningkatkan Brand Awareness di Era E-Commerce - Muhammad Rifaldi; Sri Hartati; Muhammad Alfin Vajriansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research explores digital marketing strategies aimed at enhancing brand awareness in the e-commerce era. With the significant shift towards online shopping, brand awareness has become a critical component for businesses. The study utilizes qualitative methods to gather insights on user experiences and perceptions regarding digital marketing and brand awareness. Findings indicate that effective digital marketing strategies, including social media engagement, influencer collaborations, and data analysis, significantly influence brand visibility and consumer interaction. The implications suggest that businesses must adapt their marketing strategies to leverage digital platforms for improved consumer connections and brand recognition..